EFEKTIVITAS PENGGUNAAN CANVA DAN BLOOKET-QUIZ PADA MATERI KETENAGAKERJAAN TERHADAP PEMAHAMAN SISWA KELAS XI INGLANFIS 1 DI SMAN 1 PERCUT SEI TUAN - Silvia Annur Hasibuan; Monika Flora Manik; Rini Khairani Harahap; Amelia; Divo Valentino Siboro; Revita Yuni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to determine the effectiveness of using Canva and Blooket-Quiz learning media on students’ understanding of employment material in Class XI Inglanfis 1 at SMA Negeri 1 Percut Sei Tuan. The study was conducted due to the low level of students’ understanding and participation in learning activities caused by the use of conventional teaching methods. This research employed a quantitative approach with a pre-experimental design using a one-group pretest-posttest model. The sample consisted of 29 students selected through purposive sampling. Data were collected through tests, observations, documentation, and questionnaires, and analyzed using descriptive and inferential statistics with IBM SPSS Statistics. The results showed that Canva had a positive and significant effect on students’ understanding with a significance value of 0.008 (<0.05), while Blooket-Quiz also had a positive and significant effect with a significance value of 0.000 (<0.05). Simultaneously, Canva and Blooket-Quiz significantly influenced students’ understanding, as indicated by an F-value significance of 0.000. The coefficient of determination (R²) was 0.726, indicating that 72.6% of the variation in students’ understanding could be explained by the use of Canva and Blooket-Quiz. Therefore, the integration of Canva and Blooket-Quiz is effective in improving students’ understanding of employment material and creating a more interactive and engaging learning environment.